2016
DOI: 10.1021/acs.jmedchem.6b01310
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Ruzasvir (MK-8408): A Potent, Pan-Genotype HCV NS5A Inhibitor with Optimized Activity against Common Resistance-Associated Polymorphisms

Abstract: We describe the research that led to the discovery of compound 40 (ruzasvir, MK-8408), a pan-genotypic HCV nonstructural protein 5A (NS5A) inhibitor with a "flat" GT1 mutant profile. This NS5A inhibitor contains a unique tetracyclic indole core while maintaining the imidazole-proline-valine Moc motifs of our previous NS5A inhibitors. Compound 40 is currently in early clinical trials and is under evaluation as part of an all-oral DAA regimen for the treatment of chronic HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
(58 reference statements)
0
26
0
Order By: Relevance
“…[1,2-c] [1,3] benzoxazine-3,10-diyl]bis[1H-imidazole-5,2-diyl-(2S)-2,1-pyrrolidinediyl[(1S)-1-(1-methylethyl)-2-oxo-2, 1-ethanediyl]]]bis[carbamic acid] C,C=-dimethyl ester (Fig. 2), an NS5A inhibitor, was prepared as reported previously (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2-c] [1,3] benzoxazine-3,10-diyl]bis[1H-imidazole-5,2-diyl-(2S)-2,1-pyrrolidinediyl[(1S)-1-(1-methylethyl)-2-oxo-2, 1-ethanediyl]]]bis[carbamic acid] C,C=-dimethyl ester (Fig. 2), an NS5A inhibitor, was prepared as reported previously (38).…”
Section: Discussionmentioning
confidence: 99%
“…We initiated an effort to synthesize a novel pangenotype NS5A inhibitor with a higher barrier to resistance and improved activity against the common RASs (28-37). Our efforts culminated in the discovery of ruzasvir (RZR) (formerly MK-8408), which has shown robust efficacy in patients infected with HCV (38). In this report, we summarize the preclinical antiviral characterization of ruzasvir that led to its clinical development for HCV infection.…”
mentioning
confidence: 99%
“…In addition to the high prevalence of RASs, the C‐SURGE population was enriched for cirrhosis (43%) and GT1a infection (86%). The enhanced activity of ruzasvir against common NS5A RASs in GT1 infection, including Y93H, combined with the high barrier to resistance of a three‐drug regimen (including a nucleotide inhibitor), likely contributed to the high efficacy …”
Section: Discussionmentioning
confidence: 99%
“…The development of regimens that include new members of a drug class with potency against RASs may further bolster the efficacy of triple‐drug regimens. The combination of grazoprevir, an NS3/4A protease inhibitor, ruzasvir (MK‐8408), a next‐generation pan‐genotypic NS5A inhibitor, and uprifosbuvir (MK‐3682), an NS5B polymerase nucleotide inhibitor, is under evaluation as a fixed‐dose combination for the treatment of HCV infection. In the phase 2 C‐CREST studies, this combination administered for 8, 12, or 16 weeks was highly effective in treatment‐naïve GT1‐, 2‐, or 3‐infected participants with or without cirrhosis (Child‐Pugh class A), even among those with naturally occurring NS3 or NS5A RASs .…”
mentioning
confidence: 99%
“…The most recent study suggested that NS5A was a key factor in HCV treatment (Ikeda et al, 2016). Moreover, many NS5A inhibitors have been proven to effectively treat HCV (Gane et al, 2016), such as BMS-790052 (Gao et al, 2010), MK-8742 (Coburn et al, 2013; Yu et al, 2016), MK-8408 (Ling et al, 2016), ABT530 (Lin et al, 2015), GS-5816 (Mogalian et al, 2015), etc. Because drugs are expensive and have a resistance barrier, it is essential to identify the NS5A inhibition mechanism that can offer a new strategy for the future treatment of HCV.…”
Section: Introductionmentioning
confidence: 99%